'What was all this except the lesson of life?': Browning's Fifine at the Fair and Shelley. (2nd January 2016) - Suzuki, Rieko
Abstract : This essay argues that Browning's 'most metaphysical and boldest' poem after Sordello, Fifine at the Fair, is also a poem in which Percy Shelley's influence can be detected. I have argued elsewhere for the influence of Shelley on Browning in Sordello and Browning returned to address issues that Shelley raised in 'The Triumph of Life' in Fifine . Although it is often thought that Browning moved away from Shelley after discovering the Harriet letters, I argue that he worked out his attitude towards Shelley in Fifine through the concepts of 'falsehood' and 'truth'. As for his engagement with Romanticism, Browning criticizes the condescending attitude that the speaker–narrator takes in 'The Triumph' towards the people to embrace humanity in its flawed state. He also engages with the moral dilemma that was central to 'The Triumph' by working out the protagonist's relationship with two female figures – Elvire and Fifine. As a result, the essay concludes that Fifine can be seen as a direct response to Shelley's 'The Triumph'.